Clinically led performance management in secondary healthcare: evaluating the attitudes of medical and non-clinical managers. Issue 3 (27th January 2015) - Trebble, Timothy M; Paul, Maureen; Hockey, Peter M; Heyworth, Nicola; Humphrey, Rachael; Powell, Timothy; Clarke, Nicholas
Abstract : Introduction: Improving the quality and activity of clinicians' practice improves patient care. Performance-related human resource management (HRM) is an established approach to improving individual practice but with limited use among clinicians. A framework for performance-related HRM was developed from successful practice in non-healthcare organisations centred on distributive leadership and locally provided, validated and interpreted performance measurement. This study evaluated the response of medical and non-clinical managers to its implementation into a large secondary healthcare organisation. Methods: A semistructured qualitative questionnaire was developed from themes identified during framework implementation and included attitudes to previous approaches to measuring doctors' performance, and the structure and response to implementation of the performance-related HRM framework. Responses were analysed through a process of data summarising and categorising. Results: A total of 29, from an invited cohort of 31, medical and non-clinical managers from departmental to executive level were interviewed. Three themes were identified: (1) previous systems of managing clinical performance were considered to be ineffective due to insufficient empowerment of medical managers and poor quality of available performance data; (2) the implemented framework was considered to address these needs and was positively received by medical and non-clinical managers; (3) introduction of performance-related HRM required the involvement of the whole organisation to executive level and inclusion within organisational strategy, structure and training. Conclusions: This study suggests that a performance-related HRM framework may facilitate the management of clinical performance in secondary healthcare, but is dependent on the design and methods of application used. Such approaches contrast with those currently proposed for clinicians in secondary healthcare in the UK and suggest that alternative strategies should be considered.